(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Lakes all across the world have been severely altered or deteriorated at a rate far faster than their rehabilitation. Dal Lake, in the heart of Srinagar, Jammu and Kashmir’s summer capital, has seen a dramatic decline in water quality due to anthropogenic stresses over the previous four decades, rendering it unfit for domestic usage and aesthetic purposes. The problems of sewage disposal and contamination of surface waters in lakes are rapidly rising as a result of urbanization, modernization, and population development. The discharge of untreated sewage, agricultural runoff, and silt from adjacent catchments has degraded the lake’s water quality even more. Variations in water quality can be seen in the physio chemical characteristics of the lake waters. Substances such as phosphates, nitrates, and chlorides have increased while the lake’s transparency and dissolved oxygen levels have decreased. The goal of this project is to look into and explain how sewage treatment plant effluent affects water quality, as well as to describe the current state of the lake’s water quality.